Sunday

April 20, 2014

April 20, 2014

Posted by **shefeena** on Tuesday, August 28, 2012 at 10:51am.

- maths -
**Reiny**, Tuesday, August 28, 2012 at 10:57amproduct of 5/9 and -6/5

= (5/9)(-6/5) = -2/3

difference of 5/9 and -6/5

= 5/9 + 6/5 = 79/45

so now we divide thos

-2/3 ÷ 79/45

= (-2/3)(45/79) = -30/79

check:

http://www.google.com/search?hl=en&site=&source=hp&q=%285%2F9%29%28-6%2F5%29%2F%285%2F9-%28-6%2F5%29%29&oq=%285%2F9%29%28-6%2F5%29%2F%285%2F9-%28-6%2F5%29%29&gs_l=hp.3...10096.83718.0.85636.24.24.0.0.0.0.113.1513.23j1.24.0.les%3B..0.0...1c.rLKI5N6sp_U

**Related Questions**

Math - When given sin(5x)=0, and asked to find x, I would basically have to ...

math - what is z cube 3 plus z squared minus 7z-7 divide z squared minus 3z ...

maths - DIVIDE X^6 -7^3 -8 BY THE PRODUCT OF X+1 AND ( X^2 +4) ?????

maths - DIVIDE X^6 - 7X^3 - 8 BY THE PRODUCT OF X+1 AND (X^2 + 4) ???????

alegbra - what is the product of the solutions to the equation x squared minus ...

bryce - can someone help me write out these expressions? 4 more than p: product ...

Math - Find the value of k such that the quadritic poly 3x square plus 2 kx plus...

Math - Find the value of k such that the quadritic poly 3x square plus 2 kx plus...

Math - Find the value of k such that the quadritic poly 3x square plus 2 kx plus...

Math - Find the value of k such that the quadritic poly 3x square plus 2 kx plus...